Ternary dispersions to enhance solubility of poorly water soluble antioxidants - Kakran, Mitali (2013)
The main aim of this study was to enhance the solubility and dissolution rate of the two poorly water-soluble antioxidants, curcumin (CUR) and hesperetin (HSP). Binary dispersions of the two drugs in the polymer, polyvinylpyrrolidone (PVP) or polyethylene glycol (PEG) matrix were prepared. A surfactant (Pluronic F127 or Tween 80) was also combined with the polymer to develop ternary solid dispersions to further improve the dissolution properties of CUR and HSP. The FTIR study suggested hydrogen bonding between PVP and the drugs and minor intermolecular interactions between PEG and drugs. PVP showed better amorphizing nature than PEG as inferred from the DSC and XRD study. The surfactants added in the ternary dispersions further enhanced the intermolecular interaction of the polymers with the drugs. The 2D micro-Raman spectroscopic mapping showed that after adding the surfactants in the ternary dispersions, CUR and HSP were more uniformly distributed in the PEG matrix. The solubility and dissolution rates of CUR and HSP were increased by dispersing them in the polymer matrix and the increase was dramatic when the surfactant was added to the dispersion system. The intermolecular interactions between drug and carriers led to better dispersion of drug in the polymer matrix and reduction in the size of drug particles; increase in the amorphous nature, decrease in surface tension and increase in the wettability which resulted in enhanced solubility and dissolution of the ternary dispersions. The ternary dispersions also presented better long term stability in terms of the amorphous nature and the dissolution properties.